PENERAPAN KOMPLEKSITAS WAKTU ALGORITMA PRIM UNTUK MENGHITUNG KEMAMPUAN KOMPUTER DALAM MELAKSANAKAN PERINTAH - Nugraha, Deny Wiria (FORISTEK : Forum Teknik Elektro dan Teknologi Informasi, 2012)
Abstract - The purpose of this study is to develop the software using both Delphi 7 and ArcView GIS 3.3 programming language which is able to apply Prim's algorithm in obtaining the time complexity used to calculate the cability of computer in executing the command. This study not only compares two pieces of software built by the authors but also compares the cability of two computers that each have different specifications. It has been proven that the software generated in this study can be utilized to get the complexity of time by using Prim’s algorithm which is used to calculate the ability of computer in executing the command. The software can also accurately display the minimum spanning tree as a result of applying the Prim's algorithm. The capability of computer is examined in terms of the accuracy and speed in executing the commands. The examination result shows that the capability of the first computer specifications is higher than the capability of the second computer specifications in applying the Prim's algorithm. The other result found in this study shows that the computation time software built in Delphi 7 is faster than the computation time software built in ArcView GIS 3.3. This result indicates that in terms of applying the Prim's algorithm, the software built in Delphi 7 is more efficient than the software built in ArcView GIS 3.3. Keywords: Time Complexity, Prim’s Algorithm, The Ability of Computer